1991
DOI: 10.1103/physrevlett.66.3199
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer-resolved detection of magnetic hyperfine fields at Cu/Ni(111) interfaces

Abstract: The magnetic behavior of the bordering Ni and Cu monolayers at the interface of ultrathin Cu films on Ni(lll) has been investigated. m In probes have been used, utilizing perturbed yy angular correlations, to study strength, orientation, and temperature dependence of the magnetic hyperfine field at the probe nuclear site. This magnetic hyperfine field is strongly reduced to about 50% in the first Ni layer covered by Cu; it vanishes in the adjacent Cu layer. The results are compared to hyperfine fields at free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
18
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…The absolute value of B hf at 111 Cd in the Pd adlayer is tentatively even stronger as compared with the value in the topmost layer of Ni, indicating that the magnetic polarization is rather strong in the isoelectric Pd layer with direct contact to Ni. At a comparable position in the Ni/Cu system B hf is zero [20]. The strong polarization in the adlayer propagates the polarization into the second Pd layer with a smaller, although still measurable value.…”
mentioning
confidence: 90%
“…The absolute value of B hf at 111 Cd in the Pd adlayer is tentatively even stronger as compared with the value in the topmost layer of Ni, indicating that the magnetic polarization is rather strong in the isoelectric Pd layer with direct contact to Ni. At a comparable position in the Ni/Cu system B hf is zero [20]. The strong polarization in the adlayer propagates the polarization into the second Pd layer with a smaller, although still measurable value.…”
mentioning
confidence: 90%
“…One way to measure magnetic properties on the atomic scale is offered by the use of radioactive probe atoms and the observation of their interaction with the immediate environment. Applying hyperfine-interaction techniques, monolayer-resolved studies are possible [2,3] because of the short range of the hyperfine interaction, where essentially only the nearest neighbors (quantitatively expressed in the coordination number NN) contribute to the interaction. Nuclear methods, in particular, the perturbed angular correlation spectroscopy (PAC), have an extremely high sensitivity.…”
mentioning
confidence: 99%
“…A distinction of the different fractions is obtained by the observation of their increase and decrease with increasing temperature. By this we follow a well established procedure for the same PAC probe with measured EFGs on similar surfaces, e.g., Ni(111) [2,12]; Cu(111), Cu(001) [8]; Pd(111) [14], Pd(001) [15]. At room temperature, the probes are incorporated into steps or even into the terraces.…”
mentioning
confidence: 99%
“…15 It has been suggested that the magnetic moment decreases only in the first Ni layer of a single crystal covered by Cu layers. 16 Nevertheless, a large discrepancy still exist between the experimental data 17 and the theoretical estimates of the magnetic moment in the few monolayer limit. 14,15 It has been observed that the orientation of magnetization in epitaxial Ni films depends on the film thickness.…”
mentioning
confidence: 99%